Kritik Nalar Sekuler: Perspektif Oksidentalisme Ismail Raji Al-Faruqi terhadap Peradaban Barat - Bahri, Fajar Nur; Lubis, Rizal; Siagian, Suwandi Mikail; Ekowati, Endang (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2025)
Relations between East and West in modern scholarly studies have long been dominated by Orientalism, which positions the East as an object of analysis and places it in a subordinate relationship to the West. As a critical response to this dominance, Occidentalism emerges as an approach that examines the West from non-Western perspectives in a reflective and critical manner. Ismail Raji Al-Faruqi is one of the contemporary Muslim thinkers who holds a strategic position within this discourse, particularly through his critique of the secular rational foundations that underpin modern Western civilization. This study aims to analyze Al-Faruqi’s Occidentalist perspective in criticizing Western secular rationality and its implications for the crisis of modern civilization. The research employs a qualitative method with a library research approach, focusing on an analysis of Al-Faruqi’s major works and other relevant literature. The findings indicate several key points: first, Western secularism is regarded by Al-Faruqi as the primary cause of the dichotomy between religion, science, and ethics; second, secular rationality is considered to have failed to provide a transcendent foundation and moral purpose for human life; third, Western epistemological hegemony has generated a global humanitarian and moral crisis; and fourth, the principle of tawḥīd is proposed as an alternative, integrative, and holistic paradigm for civilizational development.